Pengaruh Adopsi Financial Technology Dan Literasi Keuangan Terhadap Kepatuhan Pajak Umkm Kota Tangerang Selatan : (Studi Kasus Pada Umkm Pondok Aren) - Windi Nurcahyani; Danang Choirul Umam (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract. This study aims to examine the effect of Financial Technology adoption and financial literacy on tax compliance of MSMEs registered in Pondok Aren. The research data were obtained through the distribution of questionnaires to 114 respondents. The analytical method used in this study was multiple linear regression with the assistance of SPSS version 27. The results of the t-test indicate that Financial Technology adoption (X₁) has a positive and significant effect on MSME tax compliance (Y), which means that the higher the level of Financial Technology utilization by MSME actors, the higher their level of tax compliance. Financial literacy (X₂) also has a positive and significant effect on MSME tax compliance, indicating that better financial understanding and financial management capabilities lead to higher compliance in fulfilling tax obligations. The results of the F-test show that Financial Technology adoption and financial literacy simultaneously have a significant effect on MSME tax compliance. The coefficient of determination indicates that 40.9% of the variation in MSME tax compliance can be explained by these two variables, while the remaining portion is influenced by other variables outside the research model. These findings indicate that improving financial literacy and optimizing the use of Financial Technology play an important role in enhancing MSME tax compliance in Pondok Aren District, South Tangerang City. Keywords: Financial Technology Adoption, Financial Literacy,Tax Compliance, MSMEs in Pondok Aren.